Comparative analyses of IGA1 binding lectins from seeds of 6 distinct clones of artocarpus-integer - Hashim, Onn Haji; Gendeh, G.S.; Jaafar, M.I.N. (1993)
Purified lectins from seeds of six distinct clones of Artocarpus integer (lectin C) were shown to be structurally and functionally similar. All lectins comprised of two types of non-covalently-linked subunits with apparent M(r) of 13,300 and 16,000. The lectins appeared to interact with several human serum proteins, with the predominance of the IgA1 and C1 inhibitor molecules. Interaction was not detected with IgA2, IgD, IgG and IgM. The lectin Cs were also shown to precipitate monkey, sheep, rabbit, cat, hamster, rat and guinea-pig serum. Due to their uniform properties, lectin C may provide better alternative to the Artocarpus heterophyllus lectin, jacalin, for use in future investigations.